Health Reform in the Midst of a Social and Political Crisis in Chile, 2019-2020 - Thomas J. Bossert; Pablo Villalobos Dintrans (Taylor & Francis Group, 2020)
The protests in Chile in October 2019 raised the issue of health reform to the public agenda again. This article reviews some of the explanations for why there was a widespread protest, including the expectations of continued progress, the emergence of a "fear-based populism" and the decline in legitimacy of most social and political actors. Using the theories of Kingdon to explain how reforms are placed on the political agenda, we describe how the protests raised health reform as a problem to be addressed, discuss the tendency toward consensus on policy options by technical health reform advocates, and examine the uncertain political processes that would be necessary for a consensus reform to be adopted and implemented. A lesson for reformers is the need to pay attention to growing signs of popular resentment over failures of health reforms to address accumulating problems and to try to address them with urgency to avoid populist crises.